Dynamics of Skin Mycobiome in Infants - Zhu, Ting; Duan, Yuan-Yuan; Kong, Fan-Qi; Galzote, Carlos; Quan, Zhe-Xue (Frontiers in Microbiology, 2020)
Understanding the microbial community structure of the human skin is important for treating cutaneous diseases; however, little is known regarding skin fungal communities (mycobiomes). The aim of the present study was to investigate the features of and variations in skin fungal communities during infancy in 110 subjects less than 6 months of age. Skin samples were obtained from the back, antecubital fossa, and volar forearm, while physiological parameters including transepidermal water loss, pH, surface moisture, and deep layer hydration were evaluated. Skin fungal diversity decreased after the first three months of life. Differences in fungal community composition were greater among individual infants than among the three skin sites in the same individual. Inter- and intra-individual variation were similar and lower, respectively, than the variability between two samples obtained 12 weeks apart, from the same site in the same subject, suggesting low stability of fungal communities on infant skin. Skin physiological parameters showed little correlation with skin fungal community structure. Additionally, Malassezia was the most represented genus (36.43%) and M. globosa was the most abundant species with its abundance decreasing from 54.06% at 0–2 months to 34.54% at 5–6 months. These findings provide a basis for investigating the causative fungi-skin interactions associated with skin diseases.